Design and business: growing up as a separate couple - Duarte de Almeida, I.; Delgado, M. J.; Vilas-Boas, J.; Monteiro, J. P.; Montagna, G. (Advances in Intelligent Systems and Computing, 2019)
This paper addresses the difficulties faced by postgraduate design students (DS) and professional designers (PD) concerning the design, development and implementation of business projects (BP), and of sustainable management (SM). The DS have not previously attended any specific course, either dealing with BP, or having had training in SM. A test administered to 60 DS enabled to picture issues regarding: (i) the sense of discomfort regarding business and management areas, due to lack of skills, and (ii) the special requirements for skills in unfamiliar areas such as production, management, marketing and product stewardship. The study determined that DS perceive the need for educational policies that allow the acquisition of new skills in the referred areas. However, it seems that they are not sensitive to BP/SM scientific’ research importance. Findings point out a direction to curriculum development to bridge Design and Business areas, by overcoming the identified gap.